Rethinking media coverage vertical mediation and the war on terror - Parks, Lisa (Routledge, Taylor & Francis Group, 2018)
In the post-9/11 era, media technologies have become increasingly intertwined with vertical power as airwaves, airports, air space, and orbit have been commandeered to support national security and defense. This book develops the concept of vertical mediation to explore how audiovisual cultures enact and infer power relations far beyond the screen. Focusing on TV news, airport checkpoints, satellite imagery, and drone media, the book demonstrates how "coverage" makes vertical space intelligible to global publics in new ways and powerfully reveals what is at stake in controlling it.